If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 3.5x + -7 Reorder the terms: Y = -7 + 3.5x Solving Y = -7 + 3.5x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -7 + 3.5x
| 5y=8x-80 | | 8x^6-32x^5+4x^4= | | f(-5)=-3x+4 | | 3/p-5=-14 | | 5(13+k)= | | (10a+4)= | | 2x+3x*y=3 | | 5.54x+100=30.6916+10x | | 4x1/1.2 | | 3x-5+4x=-40 | | f(-5)=3x+4 | | (10a-4)= | | 6r+r=6r-5 | | 17x=1.3 | | 10/11x-9/11=4 | | 33-12x+25x=-6 | | 72+3x=7x-10 | | 7(r-9)=35 | | 1/2x^5=512 | | 72=4x-10 | | 2(2x+6)+8-3=14+11+15 | | Y-2=9(9x+6) | | b+10=6b | | 1/2×=13 | | 5x+10-15x=30 | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999= | | y=4x^(2/3) | | 4(j+6)=72 | | 5x-10=440 | | -7x+6-9x=6 | | 3(5.45)-7y=3 | | 10c-14=86 |